THE INFLUENCE OF PROMOTION AND TESTIMONIALS ON PURCHASE INTENTION FOR FACIAL TREATMENT SERVICES AT JESSIVA SKIN CLINIC IN TANGERANG - Frilly Rezzica Angelina; Rini Mardikawanty; Nur Haris Ependi (ASIAN PUBLISHER, 2025)
This study aims to analyze the influence of promotion and testimonials on purchase intention for facial treatment services at Jessiva Skin Clinic in Tangerang. Using a quantitative approach with a survey method, the research was conducted from January to March 2025 with a population of 100 clinic customers and a sample of 80 respondents selected through purposive sampling technique. Data were collected using questionnaires that had been tested for validity (r-value > 0.2199) and reliability (Cronbach's Alpha: promotion = 0.935, testimonials = 0.926, purchase intention = 0.896). The research variables were operationalized as follows: promotion (X1) was measured using 20 indicators, testimonials (X2) using 15 indicators, and purchase intention (Y) using 20 indicators based on a 5-point Likert scale. Data analysis employed multiple linear regression after meeting classical assumption tests, including the Kolmogorov-Smirnov normality test (p = 0.200), multicollinearity test (VIF = 2.049), and Glejser heteroscedasticity test (p > 0.05). The results show that partially, promotion has a significant effect on purchase intention (β = 0.548; p = 0.000), as do testimonials (β = 0.252; p = 0.022). Simultaneously, both variables explain 56.2% of the variance in purchase intention (R² = 0.562) with an F-value of 49.476 (p = 0.000). The study concludes that an integrated marketing strategy combining promotion and testimonials is effective in increasing purchase intention. It is recommended that the clinic optimize digital promotional content and implement a testimonial verification system to enhance credibility.